PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS KARAKTER ISLAMI MELALUI PENDEKATAN SAINTIFIK PADA MATA PELAJARAN FISIKA DALAM KURIKULUM 2013 - Muhammad Ali (Wacana Didaktika, 2019)
Abstract: The general objective of this study is to determine the feasibility of Student Worksheets (LKPD) that are suitable for use in learning, while the specific purpose is to describe the validity of LKPD, the practicality of LKPD, and the effectiveness of LKPD. This research is a development study using the ADDIE development model. The subjects of Islamic character-based LKPD trials in this study were students of SMA Negeri 2 Kotabaru. The data of this study were obtained through validation sheets, student and teacher response questionnaires, and learning achievement tests. The results of the teaching material development research show that: (1) the validation of LKPD based on Islamic characters is seen from the aspect of content and appearance with values ​​of 81.20% and 80.65%, (2) the effectiveness of Islamic character-based LKPD seen from the calculation of N-gain scores namely 0.82 which is categorized high, (3) practicality of Islamic character-based LKPD seen from the responses of students and teachers with an average score of 3.41 in practical categories. The conclusion of this study is that Islamic character-based LKPD in physics subject is suitable for use in learning and can improve student learning outcomes. Keyword: ADDIE, Islamic Character, Scientific Approach.